The impact of the law 10,267/2001 in the brazilian rural registration - Rosalen, David L. [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2014)
The publication of the Law 10,267 of 08/28/2001 changed the paradigm of rural registration in Brazil, because this law known as the Law of Georeferencing has created the National Registration of Rural Property, that unifies in a common basis different registrations present in several government agencies, such as the National Institute for Colonization and Agrarian Reform (INCRA), the Secretariat of Federal Revenue, the Brazilian Institute of Environment and Natural Resources, and the National Indian Foundation. Also, this new registration system has a graphical component which has not existed until such date, where the boundaries of rural property are georeferenced to the Brazilian Geodetic System. This new paradigm has resulted in a standardization of the survey and its representation of rural properties according to the Technical Standard for Georeferencing of Rural Properties, published by INCRA in compliance with the new legislation. Due to the georeferencing, the creation of a public GIS of free access on the Internet was possible. Among the difficulties found it may be observed the great Brazilian territory, the need for specialized professionals, and especially the certification process that INCRA has to perform for each georeferenced property. It is hoped that this last difficulty is solved with the implementation of the Land Management System that will allow automated and online certification, making the process more transparent, agile and fast.

A publicação da Lei 10.267, de 28-08-2001, alterou o paradigma do cadastro rural brasileiro, pois essa lei, conhecida como Lei do Georreferenciamento, criou o Cadastro Nacional de Imóveis Rurais, que unifica, em uma base comum, diferentes cadastros presentes em vários órgãos governamentais, como do Instituto Nacional de Colonização e Reforma Agrária (INCRA), da Secretaria da Receita Federal, do Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais e da Fundação Nacional do Índio. Também, esse novo sistema cadastral tem uma componente gráfica até então inexistente, em que os limites do imóvel rural são georreferenciados ao Sistema Geodésico Brasileiro. Esse novo paradigma teve como consequência uma padronização no levantamento de campo e respectiva representação dos imóveis rurais, conforme a Norma Técnica para Georreferenciamento de Imóveis Rurais, publicada pelo INCRA, em atendimento à nova legislação. Graças ao georreferenciamento, possibilitou-se a criação de um SIG público de acesso gratuito via Internet. Como dificuldades, temos a grande extensão territorial brasileira, necessidade de profissionais especializados e, principalmente, o processo de certificação que o INCRA tem de realizar para cada imóvel georreferenciado. Espera-se que essa última dificuldade seja sanada com a implantação do Sistema de Gestão Fundiária, que permitirá a certificação automatizada e online, tornando o processo mais transparente, ágil e rápido.
O impacto da lei 10.267/2001 no cadastro rural brasileiro
Keywords: georeferencing; registration; planning; Georreferenciamento; cadastro; planejamento rural